Association between glycemic control, age, and outcomes among intensively treated patients with acute myeloid leukemia - Kuhlman, Patrick (Support Care Cancer, 2018)
PURPOSE: To investigate the impact of hyperglycemia and glycemic variability during intensive acute myeloid leukemia therapy (AML) on outcomes by age. METHODS: Retrospective study of 262 consecutive patients with newly diagnosed AML hospitalized for intensive induction. Hyperglycemia was assessed by mean blood glucose (BG) (mg/dL) during hospitalization and glycemic variability was determined by the standard deviation (SD) of mean BG. Outcomes were complete remission ± incomplete count recovery (CR + CRi), and overall survival (OS). We used logistic regression to evaluate CR + CRi, and Cox proportional hazard models for OS, stratified by age (< 60 vs ≥ 60 years). RESULTS: Older patients (N = 138, median age 70) had higher baseline comorbidity (CCI > 1 60.1% vs 25.8%) and prevalence of diabetes (20.3% vs 7.3%) compared to younger (N = 124, median age 47). The mean ± SD number of BG values obtained per patient during hospitalization was 61 ± 71. The mean (± SD) glucose (mg/dL) during hospitalization was 121.7 (25.9) in older patients (≥ 60 years) versus 111.6 (16.4) in younger. In older patients, higher mean glucose and greater glycemic variability were associated with lower odds of remission (OR 0.80, 95% CI 0.69–0.93 and OR 0.73, 95% CI 0.61–0.88 respectively, per 10-unit increase) and higher mortality rates (HR 1.13, 95% CI 1.05–1.21 and HR 1.17, 95% CI 1.09–1.26, respectively, per 10-unit increase) in multivariate analyses. CONCLUSIONS: Our observations that hyperglycemia and increased glycemic variability were associated with lower remission rates and increased mortality in older patients suggest glycemic control may be a potentially modifiable factor to improve AML outcomes.